The Correlation between the Students’ Reading Habit towardtheStudents’ Vocabulary Mastery - Ahmad Munawir; Yulia Rahayu Ramli (Institut Agama Islam Negeri Palopo, 2021)
The objective of this study was to find out the correlation between students’ reading habit and vocabulary mastery at the second-grade students’ in SMA Negeri 1 Campalagian in the academic year 2019/2020. This study was a quantitative correlational study. The population of this study was all second-grade students with 384 total numbers of students which was divided into 11 classes. A class was selected as samples with 33 total numbers of students by using the cluster random sampling technique. In collecting the data, the researchers distributed a questionnaire to measure students’ reading habits and a test to measure students’ vocabulary mastery. In analyzing the data, the researchers used Pearson Product Moment formula. From the data analyzed, the results showed the correlation coefficient was higher than the r table (0,448 > 0.442). Additionally, the value of significance (Sig. 2-tailed) was 0,009 and lower than 0.05. Therefore, the results indicated that there was positive correlation between students’ reading habit and vocabulary mastery.